Electrical-distance driven peer-to-peer energy trading in a low-voltage network. (1st April 2021) - Guerrero, Jaysson; Sok, Bunyim; Chapman, Archie C.; Verbič, Gregor
Abstract: Given the increasing penetration of distributed energy resources (DER) in low-voltage networks, peer-to-peer (P2P) energy trading has been proposed to facilitate DER integration into power systems. In this paper, we investigate P2P energy trading driven by the electrical distance between agents in a low-voltage network. Our market design considers the role of a distributed system operator (DSO) who determines the shortest path between agents, encoded in preference lists. The DSO submits the preference lists to the agents but does not intervene in the P2P matching process. Specifically, we propose two decentralised P2P market mechanisms that are induced by the relations in the preference lists. First, we introduce a stable-matching (SM) algorithm for matching agents and guaranteeing that no agents want to mutually deviate from the matching. Second, a mechanism based on a continuous double auction (CDA) is adopted for continually matching peers. The proposed mechanisms are tested on a UK low-voltage network. Simulation results show that the outcome of the proposed SM mechanism faces a trade-off between the stability of the matching and market efficiency, whereas the proposed CDA-based mechanism deviates from the stable outcome but can still capture the high market efficiency of the CDA. We show that a P2P market driven by electrical distance leads to reduced losses and line congestion in both mechanisms. Highlights: We introduced a novel decentralised electrical-distance driven P2P market design. We proposed a stable-matching and a CDA-based mechanisms for matching peers. The shortest paths between agents are encoded in preference lists by a DSO. Technical implications of adopting the proposed mechanisms are assessed. Inciting P2P trading between closer agents reduces power losses and congestion.